Одесский НИИ ТТ: тридцать лет в телевизионной технике - Belyavsky, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The article highlights the history and achievements of the Odessa Research Institute of Television Technology. It traces the institute’s development from its early experiments to the creation of advanced broadcasting systems, emphasizing its contribution to the evolution of television in Ukraine and the role of its engineers and scientists in advancing the field. The publication is valuable for scholars of technology history and professionals in telecommunications.